Long-term health impact assessment of total PM2.5 in Europe during the 1990–2015 period. (July 2019) - Ciarelli, Giancarlo; Colette, Augustin; Schucht, Simone; Beekmann, Matthias; Andersson, Camilla; Manders-Groot, Astrid; Mircea, Mihaela; Tsyro, Svetlana; Fagerli, Hilde; Ortiz, Alberto González; Adani, Mario; Briganti, Gino; et al.
Abstract: Several datasets of PM2.5 concentrations over Europe during the 1990–2015 period, were used to calculate health impacts from chronic exposure to total particle matter below 2.5 μm (i.e. PM2.5 ). The datasets used in the analysis include the European Topic Centre on Air Pollution and Climate Change Mitigation (ETC/ACM), the Copernicus Atmospheric Monitoring Service (CAMS), the Global Burden of Disease (GBD), the World Health Organization (WHO) as well as the EURODELTA-Trends (EDT) multi-model reanalysis developed specifically for Europe. The exposure to ambient PM2.5 concentrations was calculated as population weighted annual average PM2.5 concentrations by country. The calculated exposure to PM2.5 was later used as input in the health impact assessment (HIA) Alpha-RiskPoll (ARP) tool to retrieve the total number of premature deaths. Our results indicate a substantial reduction in the number of premature deaths from PM2.5 exposure in Europe over the 1990–2010 period, between nearly 30 and 50%. Putting all the data-sets together, even if they do not cover the whole period, a decrease of even around 60% is observed between 1990 and 2015. For the countries included in this study, the estimated number of premature deaths from PM2.5 in 1990 was found to be around 960 000 (median of all the available datasets), whereas in 2015 it was found to be around 445 000. However, the variability in the estimated premature deaths from the different PM2.5 datasets was found to be large during the early 90s (around a factor of 2). For the latest years of the investigated period (2005 onwards), where a relatively flat trend in the PM2.5 exposure was observed, the differences between the different datasets were smaller. Even though our results indicate a reduction in the number of premature deaths from chronic exposure to PM2.5, the numbers remain considerable in 2015, underlining the need to continue improving air quality in the future. Highlights: PM2.5 concentrations over Europe were used to perform a health impact assessment during the 1990–2015 period. Population weighted PM2.5 concentrations were predicted to have declined by 0.8 µg m −3 y −1 on average. The number of premature deaths due to exposure to PM2.5 was predicted to have declined during the 1990–2015 period. The variability in the predicted number of premature deaths was higher in the 1990s compared to the 2000s.